Rome Statute: Prospects of recognizing jurisdiction of the International Criminal Court - Nataliya V. Maslak, Maksym P. Kutsevych, Ruslan A. Volynets, Valentyna V. Tkachenko (Opción, 2020)
In the article, the author considers the implementation of the Rome Statute of the International Criminal Court in Ukrainian legislation. The importance of such implementation is analyzed, as well as the prospects for recognizing the jurisdiction of the International Criminal Court by national jurisdiction, as well as its authority to administer justice. The author analyzes various approaches and ways of implementing the Rome Statute into national legislation. The experience and ways of implementing the Rome Statute in the national legislation of countries such as the United Kingdom, the Netherlands, the Republic of Korea and Canada are considered.